Figurative Language Used by Characters in the Sherlock Holmes 1 Movie Script “The Study in Pink” - Agung Yustina, I Gusti Ngurah; Lirishati Soethama, Putu (Humanis; Vol 22 No 2 (2018)DO - 10.24843/JH.2018.v22.i02.p27, 2018)
The title of this study is Figurative Language Used By Characters in the Sherlock Holmes 1 Movie Script “The Study in Pink”. The aims of this study are to discover the types of figurative languages and their meanings used in the movie. The data source was taken from the internet website and this movie script was purely from the Sherlock movie in season one. In collecting data, the method used for this study was documentary method. In analyzing the data, the study used qualitative method. The major theory used is the theory of figurative language proposed by Knickerbocker and Reninger (1963) , and the supporting theory about the meaning proposed by Leech (1974). The result shows that there are four types from ten types of figurative language appearing in the movie. In addition, there are three types that are used from seven types of meaning.